2015
DOI: 10.1007/s11096-015-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring community pharmacists’ experiences of surveying patients for drug utilization research purposes

Abstract: Under certain conditions, community pharmacies are feasible as a setting for conducting patient surveys in drug utilization research, and dispensing pharmacists suitable for conducting them. When regular dispensing staff perform the survey interviews as a part of the drug dispensing process, additional resources to manage the immediate increase in work load have to be considered. Otherwise, data quality may be compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As expected, given our own experiences as well as prior research, we identified barriers including those with recruiting patients and involving staff in the research. Consistent with prior qualitative studies, we identified that time commitment was one of the greatest obstacles to conducting research in the pharmacy. An advantage of the design of our study is that interviews allowed for probing on pharmacists’ suggestions on how such a barrier may be addressed, with some pharmacists sharing that if a study cannot be synthesised within the framework of a daily pharmacy workflow, then financial incentives may offer a solution.…”
Section: Discussionmentioning
confidence: 78%
“…As expected, given our own experiences as well as prior research, we identified barriers including those with recruiting patients and involving staff in the research. Consistent with prior qualitative studies, we identified that time commitment was one of the greatest obstacles to conducting research in the pharmacy. An advantage of the design of our study is that interviews allowed for probing on pharmacists’ suggestions on how such a barrier may be addressed, with some pharmacists sharing that if a study cannot be synthesised within the framework of a daily pharmacy workflow, then financial incentives may offer a solution.…”
Section: Discussionmentioning
confidence: 78%
“…Legoinha et al (2006) suggested that each group should receive no more than 30 students and be coordinated by a tutor. However, given the sample loss of up to 70% observed in epidemiological studies involving the use of the Internet or telephone as a strategy for data collection (Chwastiak et al, 2002;Charani et al, 2013;Shcherbakova, Shepherd, 2014;Frisk et al, 2015), up to 50 participants are allocated to each group.…”
Section: Allocationmentioning
confidence: 99%